2020
DOI: 10.1007/s40256-020-00429-7
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone in the COVID-19 Era: Treatment for Symptomatic Patients Only, or Drug to Prevent Infection?

Abstract: Amiodarone, one of the most widely prescribed antiarrhythmic drugs to treat both ventricular and supraventricular arrhythmias, has been identified as a candidate drug for use against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We present the rationale of using amiodarone in the COVID-19 scenario, as well as whether or not amiodarone administration represents a potential strategy to prevent SARS-CoV-2 infection, rather than simply used to treat patients already symptomatic and/or with seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Recently, the case of a patient affected by COVID-19-related respiratory failure who recovered after only supportive measures and off-label short therapy with amiodarone (starting on the second day from admission and lasting 5 days; administered on day 1 as a 15 mg/kg/24 h intravenous infusion, followed by oral administration of 400 mg twice daily) has been reported ( Castaldo et al, 2020 ). Accordingly, amiodarone, widely prescribed to treat both ventricular and supraventricular arrhythmias, has been proposed as a possible therapy (alone or as part of a combination regimen) to prevent SARS-CoV-2 infection rather than to treat symptomatic or severe COVID-19 patients ( Aimo et al, 2020 ; Sanchis-Gomar et al, 2020 ).…”
Section: Sigma-1 Receptor Ligands Exert Antiviral Activitymentioning
confidence: 99%
“…Recently, the case of a patient affected by COVID-19-related respiratory failure who recovered after only supportive measures and off-label short therapy with amiodarone (starting on the second day from admission and lasting 5 days; administered on day 1 as a 15 mg/kg/24 h intravenous infusion, followed by oral administration of 400 mg twice daily) has been reported ( Castaldo et al, 2020 ). Accordingly, amiodarone, widely prescribed to treat both ventricular and supraventricular arrhythmias, has been proposed as a possible therapy (alone or as part of a combination regimen) to prevent SARS-CoV-2 infection rather than to treat symptomatic or severe COVID-19 patients ( Aimo et al, 2020 ; Sanchis-Gomar et al, 2020 ).…”
Section: Sigma-1 Receptor Ligands Exert Antiviral Activitymentioning
confidence: 99%
“…Drug repurposing is a popular exploratory method, including exploring new indications from old drugs [ 99 ]. Currently, most of the drugs clinically used to fight the virus are for influenza, viral hepatitis, and HIV, as well as drugs developed for MERS and SARS [ 100 - 170 ] ( Supplementary Table 1 ). However, since the viral outbreak, many exploratory clinical trials of antiviral treatments have been published.…”
Section: Current Therapeutics and Drug Developmentmentioning
confidence: 99%
“…Amiodarone, used to control a wide range of atrial and ventricular arrhythmias, has been suggested as potential drug for prevention or treatment of COVID-19 [92,98]. The ReCOVery-SIRIO, a multicenter study, aims to determine the role of amiodarone or verapamil, in hospitalised patients within the initial stage of COVID-19 [93,95].…”
Section: Antiarrhythmic Drugs (Other Than Beta-blockers)mentioning
confidence: 99%
“…Use of antiarrhythmic drugs in COVID-19 should be similar to patients in other diseases [98,101]. Dose adjustments may be needed in older patients, and with renal or hepatic impairment [92,102].…”
Section: In Conclusionmentioning
confidence: 99%